Next Generation of Information Technology in Educational Management 10th IFIP WG 3.7 Conference, ITEM 2012, Bremen, Germany, August 5-8, 2012, Revised Selected Papers - Passey, Don.; Breiter, Andreas.; Visscher, Adrie. (IFIP Advances in Information and Communication Technology,, 2013)
This book constitutes the refereed post-proceedings of the 10th IFIP WG 3.7 Conference on Information Technology in Educational Management, ITEM 2012, held in Bremen, Germany, in August 2012. The 16 revised full papers presented were carefully reviewed and selected. The papers offer an outstanding overview of the contemporary field of information technology in educational management. They focus on four key questions: Why do we need new educational management information systems? What issues face those developing new educational management information systems? What new educational management information systems are being developed? What educational management systems are already in place?